The Pselaphinae of Madagascar. II. Redescription of the genus Semiclaviger Wasmann, 1893 (Coleoptera: Staphylinidae: Pselaphinae: Clavigeritae) and synonymy of the subtribe Radamina Jeannel, 1954 - Hlaváč, Peter; Baňař, Petr; Parker, Joseph (Zootaxa, 2013)
The enigmatic Madagascan genus Semiclaviger Wasmann is among the most morphologically distinct members of the obligately myrmecophilous pselaphine supertribe Clavigeritae. Here, the genus is redescribed, and the lectotype of the type species S. sikorae Wasmann is designated. We present a detailed study of the morphology of Semiclaviger, which supports its uniqueness among the Clavigeritae. The systematic position of the genus, and the validity of its subtribe Radamina, are discussed leading us to place Radamina in synonymy with Clavigerodina.